2010
DOI: 10.1007/s00417-010-1310-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual results and complications of primary intraocular lens implantation in infants aged 6 to 12 months

Abstract: Primary IOL implantation was safe and effective for infantile cataract surgery. Total or unilateral cataract, nystagmus or strabismus, and inadequate amblyopic therapy were predictors of poor BCVA. Significant myopic shifts occurred especially in infants in the first year of surgery. The pseudophakic eye had a similar growth rate, as measured by axial length, to that of the fellow normal eye, in unilateral cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
2
15
0
7
Order By: Relevance
“…Primary IOL implantation is the preferred method of optical correction in older children after lensectomy [4, 11]. A large sample study by Solebo et al [12] including 221 children under 2 years of age with congenital or infantile cataract found that IOL implantation was independently associated with better visual outcomes in bilateral but not unilateral cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary IOL implantation is the preferred method of optical correction in older children after lensectomy [4, 11]. A large sample study by Solebo et al [12] including 221 children under 2 years of age with congenital or infantile cataract found that IOL implantation was independently associated with better visual outcomes in bilateral but not unilateral cases.…”
Section: Discussionmentioning
confidence: 99%
“…Children with unilateral dense cataract tended to develop strabismus; children with bilateral dense cataract tended to develop nystagmus [4, 9, 29]. Birch et al [9] indicated that congenital cataracts with visual deprivation after more than 1.5 months were associated with a significantly higher risk for strabismus and nystagmus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in a study on primary IOL implantation in infants aged 6–12 months documented a 26.9% risk of VAO. 24 Trivedi et al . 25 reported that 23.6% of infantile cataract and primary IOL implantation, required reoperation for VAO.…”
Section: Discussionmentioning
confidence: 99%
“…The risk may increase with microcornea, microophthalmos, PFV and younger age. 24 There is some controversy about the protective role of IOL implantation against glaucoma after infantile cataract surgery. For example, a study 29 on infants who underwent cataract surgery in the 1 st year of life, found a 13% chance of glaucoma in pseudophakic eyes compared to a 33% chance of glaucoma in aphakic eyes.…”
Section: Discussionmentioning
confidence: 99%